Kesediaan laluan kerjaya dalam kalangan pelajar kerja sosial di Universiti Kebangsaan Malaysia - Nora Sawal,; Khadijah Alavi,; Fauziah Ibrahim,; Nor Jana Saim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Readiness in career can increase awareness of knowledge, skills, interests, experience, potential and personality as a professional social worker. The main purpose of this study is to explore career options of student social work to encourage career readiness level as a competent social workers. Lack of research on the issue of increasing the understanding and awareness of students in their field of study. This study was conducted by using qualitative approach based on case study. The data collection techniques were collected through structured interviews of 10 informants selected for this study using purposive sampling technique. The selected study location was at Faculty of Social Science and Humanities, UKM Bangi. The findings reveal that there are three main challenges that the student is not exposed to real social worker employment. Second, personality development as a social worker, such as communication skills, interpersonal and team work in solving individual issues. Thirdly, motivation and career paths in social work have never been disclosed to students as a competent social worker. The implication of this study suggests that the combination of teaching and learning is based on the theory and practice with government agencies to enhance workability among UKM social work graduates.